Flame-retardant nylon composite material and preparation method thereof
By using a composite flame retardant compounded with lanthanum bisaziridine diazepidyl phosphate and an environmentally friendly glassy/ceramic smoke-free halogen-free flame retardant, and adding modified expanded graphite, modified carbon nanotubes and melamine polyphosphate, the flame retardant precipitation, insufficient heat resistance and smoke generation of combustion of existing flame retardant nylon materials are solved, and efficient flame retardant performance and stability are achieved.
Patent Information
- Application Number
- CN202411878959.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
In use, existing flame retardant nylon materials have problems such as flame retardant precipitation affects the mechanical properties and flame retardant properties, insufficient heat resistance, smoke and toxic gases generated in combustion, and odor generated during injection molding and heating.
A composite flame retardant is used to combine lanthanum bisaziridine diazepidyl phosphate and environmentally friendly glassy/ceramic smokeless halogen-free flame retardant, and modified expanded graphite, modified carbon nanotubes and melamine polyphosphate are added to the composite material as composite synergists to improve flame retardant performance and stability.
It significantly improves the flame retardant performance and stability of flame retardant nylon composite materials, reduces smoke and toxic gases generated by combustion, improves the heat resistance and mechanical properties of the material, and reduces the odor of the material, improves safety and service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a flame retardant nylon composite material and a preparation method thereof. Background Art
[0002] Nylon (PA) is a polymer containing amide groups in the macromolecular main chain repeating unit. It is the common name for polyamide resin. It is the plastic variety with the largest output, the most varieties and the widest application among the five major projects, among which the output of nylon 66 and nylon 6 accounts for more than 90%. Nylon has excellent mechanical properties, heat resistance, electrical insulation properties, fatigue resistance, self-lubrication, wear resistance and easy modification and processing. It is widely used and has become an indispensable structural material in all walks of life.
[0003] The flame retardant level of nylon resin itself can reach UL94 V-2 level, and adding appropriate flame retardants to nylon resin can improve its flame retardant performance. Flame retardant nylon composite materials are widely used in daily life, including automobiles, electronic appliances, such as terminals, sockets, switches, electrical housings, automotive interior connectors, interior decoration materials, and internal parts of household appliances, so people have higher and higher requirements for their performance.
[0004] With the continuous development of science and technology, the performance requirements for materials are getting higher and higher. Flame-retardant nylon materials are widely used in many fields such as electronics, automobiles, aerospace, etc. due to their good mechanical properties and flame retardancy. However, the existing flame-retardant nylon materials still have some shortcomings in actual use: (1) Flame retardants are easy to precipitate during use, which not only affects the appearance of the material, but also may reduce the mechanical properties and flame retardancy of the material; (2) The heat resistance of flame retardants is limited and it is difficult to meet the application requirements in some high temperature environments; (3) Flame retardants will produce a large amount of smoke and toxic gases during combustion, posing a serious threat to human life and safety; (4) The addition of flame retardants may cause the material to emit odor during the injection molding heating process, affecting the overall sensory experience of the product and having adverse effects on human health. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a flame retardant nylon composite material to solve the problem that the flame retardant in the prior art cannot take into account the mechanical properties, flame retardant properties and safety performance of the nylon composite material. At the same time, the present invention will also provide a method for preparing the flame retardant nylon composite material.
[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: The first aspect of the present invention provides a flame retardant nylon composite material, comprising the following components in parts by weight: A flame retardant nylon composite material comprises the following components in parts by weight: Nylon resin: 75-90 parts; Flame retardant: 5-18 parts; Lubricant: 0.2-1 part; Antioxidant: 0.2-1 part, used to prevent oxidation of the other components mentioned above; Coupling agent: 0.2-1 part, used for surface treatment of flame retardant to improve the compatibility between flame retardant and resin.
[0007] In one embodiment of the present invention, the nylon resin is selected from one of PA6, PA66, PA610, PA1010, and PA12, or a mixture of any multiple thereof.
[0008] Furthermore, the relative viscosity of the nylon resin is 2.4 to 3.2.
[0009] In one embodiment of the present invention, the flame retardant is selected from halogen-free flame retardants, and the flame retardant includes one or a mixture of two of bis-aziridine lanthanum hypophosphite and environmentally friendly glassy / ceramic smokeless and halogen-free flame retardants.
[0010] Furthermore, the flame retardant is preferably a composite flame retardant of lanthanum bis-aziridinyl hypophosphite and an environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant.
[0011] Among them, when bis-aziridine hypophosphite is burned, nitrogen and carbon synergistically promote carbonization, forming a stable and dense carbon layer, blocking heat and oxygen, and inhibiting combustion; at the same time, bis-aziridine hypophosphite decomposes under heat to release non-flammable gases such as nitrogen, diluting the concentration of combustible gases, inhibiting chain reactions, and having a strong gas-phase flame retardant effect. Lanthanide elements themselves have excellent thermal stability, and lanthanum flame retardants can effectively play a flame retardant role in a wide temperature range. At the same time, the chemical structure of the bis-aziridine group is conducive to the production of strong interactions such as hydrogen bonds and van der Waals forces with the molecular chains of polymer materials, has good compatibility, can be evenly dispersed, is highly flame-retardant during combustion, and does not affect the physical and processing properties of the material; and the chemical bonds in the bis-aziridine structure are stable, and the thermal stability is good within the material processing temperature range, which can ensure flame retardancy during processing and use.
[0012] Among them, environmentally friendly glassy / ceramic smokeless and halogen-free flame retardants can undergo polymerization, sintering and other reactions under the action of high temperature and flame to form a ceramic-like protective layer, which can effectively prevent heat from being transferred to the surface of the protected material; at the same time, it can also prevent oxygen from contacting the combustible material below, thereby inhibiting the continued combustion. In addition, the addition of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardants reduces the smoke generated during the combustion process and improves safety when a fire occurs. At the same time, the addition of the flame retardant reduces the odor of the material, and the flame retardant also has good chemical inertness, acid and alkali resistance, solvent resistance, salt spray resistance and electrochemical stability.
[0013] Furthermore, in this composite flame retardant, the ratio of the lanthanum bis-aziridine subphosphite and the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant needs to be controlled within an appropriate range. When the ratio of the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is too large, the mechanical properties and processing properties of the nylon composite material will be reduced; when the ratio of the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is too small, it will not only reduce the flame retardant properties of the material, but also have a strong odor, and combustion will produce more dense smoke. Therefore, the mass ratio of the lanthanum bis-aziridine subphosphite and the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is 10: (0.5-4); preferably 10: (1-2).
[0014] In one embodiment of the present invention, the lubricant is selected from one or a mixture of any two of ethylene bisstearamide, ethylene acrylic acid copolymer, erucamide, silicone powder and stearate.
[0015] In one embodiment of the present invention, the antioxidant is selected from one of N,N'-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide] (i.e., oxidant 1098), tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl erythritol ester (i.e., antioxidant 1010), tris[2.4-di-tert-butylphenyl]phosphite (i.e., antioxidant 168), a mixture of phenols and phosphonates, or a mixture of any multiple thereof.
[0016] In one embodiment of the present invention, the coupling agent is selected from one of KH550, KH560, and KH570, or a mixture of any multiple thereof.
[0017] In one embodiment of the present invention, the flame retardant nylon composite material further includes 0.5 to 5 parts of a composite synergist.
[0018] Furthermore, the composite synergist comprises one or a mixture of any of modified expanded graphite, modified carbon nanotubes and polyphosphate melamine. The composite synergist is preferably a composite of modified expanded graphite, modified carbon nanotubes and polyphosphate melamine.
[0019] Furthermore, the modified expanded graphite includes a mixture of one or both of polyurethane modified expanded graphite and polytetrafluoroethylene modified expanded graphite. The expanded graphite can expand during the pyrolysis process, strengthen the carbon layer formed by the combustion of bis-aziridine lanthanum hypophosphite, increase the thickness and stability of the carbon layer, help improve the flame retardant effect, and the addition of the expanded graphite can also effectively reduce the viscosity of the nylon matrix and improve the processing performance.
[0020] Polyurethane modifies the surface of expanded graphite through its amino, hydroxyl and other active groups, which can not only enhance the compatibility of expanded graphite with the matrix material, but also enhance the expansion performance of expanded graphite. It can repair the cracks on the surface of expanded graphite during its expansion, thereby cooperating with bis-aziridine lanthanum hypophosphite to produce a more stable and comprehensive carbon layer in the flame, effectively shielding heat and significantly improving flame retardant properties.
[0021] Polytetrafluoroethylene is combined with the surface of expanded graphite by chemical grafting. On the one hand, polytetrafluoroethylene can improve the surface lubricity of expanded graphite and increase its fluidity, thereby reducing the viscosity of nylon materials and improving processing performance; on the other hand, polytetrafluoroethylene can reduce the pyrolysis rate of expanded graphite and help generate a stronger carbon layer, thereby improving the flame retardancy of the composite material.
[0022] Furthermore, the modified expanded graphite is obtained by the following preparation method: using a strong acid to perform an acid treatment on the expanded graphite to increase the oxidized groups on the surface of the expanded graphite, then washing with deionized water until neutral and drying, adding the treated expanded graphite to an organic solvent for ultrasonic dispersion, slowly adding the dissolved polyurethane solution or polytetrafluoroethylene solution to the dispersion of the expanded graphite, adding an appropriate amount of catalyst, continuously stirring and reacting for a period of time, filtering out unreacted solvents and impurities after the reaction is completed, and evaporating and drying to obtain the modified expanded graphite.
[0023] Among them, strong acids include but are not limited to concentrated nitric acid, concentrated sulfuric acid, etc.; Organic solvents include DMSO, chloroform, ethylene dichloride, or fluorinated solvents; Catalysts include organotin or amine compounds; The reaction time is 6 to 24 hours.
[0024] Furthermore, the modified carbon nanotubes include one or a mixture of any of polyvinyl polyether modified carbon nanotubes, polyvinyl alcohol modified carbon nanotubes and polyamide modified carbon nanotubes. Among them, carbon nanotubes have excellent thermal stability and thermal conductivity. Adding carbon nanotubes to the flame retardant system can not only enhance the thermal stability of the carbon layer, but also improve the dispersibility of the flame retardant, reduce heat accumulation in the composite material, and thus enhance the flame retardant effect of the flame retardant.
[0025] Polyvinyl polyether, polyvinyl alcohol and polyamide have good compatibility with the resin matrix. Combining them to the surface of carbon nanotubes can improve the dispersion of carbon nanotubes and their compatibility with the matrix material. The modified carbon nanotubes can promote the formation of the carbon layer, improve the structure of the carbon layer, and enhance the resistance of the carbon layer to high temperature and flame, thereby improving the flame retardant properties of bis-aziridine lanthanum hypophosphite and environmentally friendly glassy / ceramic smokeless and halogen-free flame retardants.
[0026] Furthermore, the modified carbon nanotubes are obtained by the following preparation method: the carbon nanotubes are treated with a strong acid, then washed with deionized water until neutral and dried, a polyvinyl polyether solution, a polyvinyl alcohol solution or a polyamide is dissolved in a solvent, and then the treated carbon nanotubes are added to the solvent for ultrasonic dispersion, and the reaction is continued for a period of time. After the reaction is completed, the unreacted solvent and impurities are filtered out, and the modified carbon nanotubes are obtained after evaporation and drying.
[0027] Wherein, the solvent includes water, chloroform or acetone; The reaction time is 6 to 24 hours.
[0028] Furthermore, in the composite synergist, the addition of melamine polyphosphate can not only improve the dispersibility of the modified expanded graphite and the modified carbon nanotubes to avoid the agglomeration of the two in the nylon matrix, but also ensure that the modified expanded graphite and the modified carbon nanotubes can be evenly distributed in the matrix, so that the two can synergize with the flame retardant to enhance the flame retardant effect; and, after thermal decomposition, melamine polyphosphate can release phosphoric acid groups and ammonia, the phosphoric acid groups can promote the formation of a carbonized layer, and the ammonia can reduce the generation of combustible gases, thereby improving the flame retardant effect.
[0029] Furthermore, the mass ratio of modified expanded graphite, modified carbon nanotubes and polyphosphate melamine in the composite synergist is (3-5): (1-2): (1-2).
[0030] A second aspect of the present invention provides a method for preparing a flame retardant nylon composite material, comprising the following steps: S1, vacuum drying the nylon resin to obtain a dried nylon resin; S2, modifying the flame retardant with a coupling agent to obtain a flame retardant modified with a coupling agent; S3, weighing the dried nylon resin, coupling agent-modified flame retardant, antioxidant, lubricant and composite synergist according to proportion, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S4, feeding the premix obtained in step S3 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
[0031] In step S1, the moisture content of the dried nylon resin is less than 0.05%.
[0032] In step S2, the process of coupling agent modified flame retardant is as follows: dissolve the coupling agent in ethanol solution, stir evenly to obtain coupling agent solution, add flame retardant to the coupling agent solution, stir and react at 70-90°C for a period of time, filter the emulsion after the reaction, collect the solid, wash and filter with anhydrous ethanol until the pH of the filtrate is neutral, collect the filtered solid and dry it to constant weight to obtain coupling agent modified flame retardant.
[0033] By first treating the flame retardant with a coupling agent and then mixing the modified flame retardant with nylon resin, the bonding force between the flame retardant and the nylon resin can be improved, thereby improving the mechanical properties of the composite material.
[0034] In step S4, the temperature of zone 1 of the twin-screw extruder is set to 180±10°C, the temperature of zones 2, 3 and 4 is set to 225±10°C, the temperature of zones 5, 6, 7 and 8 is set to 190±10°C, the temperature of the die head is set to 200±15°C, the main engine speed is set to 300-350r / min, the main engine current is 140-200A, and the main feeding speed is 10-35HZ.
[0035] As described above, the flame retardant nylon composite material and the preparation method thereof of the present invention have the following beneficial effects: 1. Compared with the traditional diethyl phosphate flame retardant, the composite flame retardant of the present invention can well improve the flame retardant performance. Among them, when the bis-aziridine hypophosphite is burned, nitrogen and carbon synergistically promote carbonization to form a stable and dense carbon layer, which blocks heat and oxygen and inhibits combustion; at the same time, the bis-aziridine hypophosphite is decomposed by heat to release non-combustible gases such as nitrogen, dilute the concentration of combustible gases, inhibit chain reactions, and have a strong gas phase flame retardant effect. The environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant can undergo polymerization, sintering and other reactions under the action of high temperature and flame to form a ceramic-like protective layer, which can effectively prevent heat from being transferred to the surface of the protected material; at the same time, it can also prevent oxygen from contacting the combustible material below, thereby inhibiting the continued combustion. The synergy between the bis-aziridine hypophosphite and the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant can further improve the flame retardant effect. Compared with traditional flame retardants, it has a high flame retardant effect and a small amount of addition.
[0036] 2. Compared with traditional flame retardants, the composite flame retardant of the present invention has good stability and safety performance. Among them, lanthanide elements themselves have excellent thermal stability, and their compounds can also maintain good structural stability and chemical stability at high temperatures. Therefore, lanthanide flame retardants can effectively play a flame retardant role in a wide temperature range, and are particularly suitable for some materials and application scenarios that require high thermal stability. At the same time, the chemical structure of the bis-aziridine group is conducive to the production of strong interactions such as hydrogen bonds and van der Waals forces with the molecular chains of polymer materials, has good compatibility, can be evenly dispersed, and is highly flame retardant during combustion without affecting the physical and processing properties of the material; and the chemical bonds in the bis-aziridine structure are stable, and the thermal stability is good within the material processing temperature range, which can ensure the flame retardancy during processing and use. Compared with the main group metal flame retardants, when the temperature is too high, there may be incomplete decomposition or loss of flame retardant effect. The bis-aziridine lanthanum hypophosphite flame retardant has higher temperature resistance, can improve the precipitation problem of flame retardants, and improve the stability and service life of materials. In addition, the addition of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardants reduces the smoke generated during combustion and improves safety in the event of a fire. At the same time, the addition of the flame retardant reduces the odor of the material. The flame retardant also has good chemical inertness, acid and alkali resistance, solvent resistance, salt spray resistance and electrochemical stability.
[0037] 3. The composite synergist of the present invention can cooperate with the composite flame retardant of the present invention to optimize the effect of the flame retardant, and improve the flame retardancy, stability and uniform dispersibility of the flame retardant. The modified expanded graphite has excellent expansion characteristics during the pyrolysis process, and can strengthen the carbon layer formed by the combustion of diaziridinyl lanthanum hypophosphite, increase the thickness and stability of the carbon layer, and repair the cracks on the carbon layer; in addition, the addition of expanded graphite can reduce the viscosity of the nylon material and improve the processing performance. The modified carbon nanotubes have good compatibility with the nylon matrix, which can promote the uniform dispersion of the flame retardant; and due to the excellent thermal conductivity of the carbon nanotubes, the heat accumulation in the composite material can be reduced, thereby enhancing the flame retardant effect of the flame retardant. The addition of melamine polyphosphate can not only improve the dispersibility of modified expanded graphite and modified carbon nanotubes, ensuring that the two can be evenly distributed in the nylon matrix, so that the two can synergize as flame retardants to enhance the flame retardant effect; moreover, melamine polyphosphate can release phosphoric acid groups and ammonia after thermal decomposition. The phosphoric acid groups can promote the formation of a carbonized layer, and the ammonia can reduce the generation of combustible gases, thereby improving the flame retardant effect.
[0038] 4. The present invention uses a composite flame retardant compounded with lanthanum bis-aziridine phosphite and an environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant. At high temperatures, lanthanum bis-aziridine phosphite produces a dense and stable carbonized layer, and the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant forms a protective layer similar to ceramics. The two synergistically protect the nylon material and have good flame retardant properties; and the two can maintain good structural stability and chemical stability at high temperatures, thereby ensuring the durability of the flame retardant effect and improving the safety of the material. In addition, the composite synergist of the present invention has a synergistic effect on the flame retardant, the modified expanded graphite can strengthen and repair the carbonized layer produced by combustion, the modified carbon nanotubes can reduce heat accumulation, and the polyphosphate melamine can further flame retardant. The three synergistically can also reduce the viscosity of the material, promote the uniform dispersion of the flame retardant in nylon, and improve the processing performance. DETAILED DESCRIPTION
[0039] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0040] Example 1 The present embodiment provides a flame-retardant nylon composite material, comprising the following components in parts by weight: 85 parts of nylon 6, 14 parts of lanthanum bisaziridinyl hypophosphite, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0041] The flame retardant nylon composite material is obtained by the following preparation method: S1. Vacuum drying the nylon resin to make its moisture content lower than 0.05%; S2, 100mL of coupling agent KH560 was mixed with 1.5L of 95% ethanol, and stirred at 50°C for 30min to obtain a coupling agent solution, and then 1000g of lanthanum diaziridine phosphite was added to the coupling agent solution, and stirred at 80°C for 6h. After the reaction was completed, the emulsion was filtered, and the solid was collected, washed with anhydrous ethanol, and filtered until the pH of the filtrate was 7. The solid after filtration was collected and placed in a vacuum oven at 100°C to dry to constant weight, and 1014.1g of coupling agent-modified lanthanum diaziridine phosphite was obtained; S3, weighing 85 parts of nylon resin, 14.2 parts of coupling agent-modified diaziridinyl lanthanum hypophosphite, 0.2 parts of antioxidant, and 0.3 parts of lubricant, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S4, feeding the premix obtained in step S3 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
[0042] Example 2 The present embodiment provides a flame-retardant nylon composite material, comprising the following components in parts by weight: 85 parts of nylon 6, 13 parts of lanthanum bis-aziridine hypophosphite, 1 part of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0043] The flame retardant nylon composite material is obtained by the following preparation method: S1. Vacuum drying the nylon resin to make its moisture content lower than 0.05%; S2, 100mL of coupling agent KH560 was mixed with 1.5L of 95% ethanol, and stirred at 50°C for 30min to obtain a coupling agent solution, and then 1000g of lanthanum diaziridine phosphite was added to the coupling agent solution, and stirred at 80°C for 6h. After the reaction was completed, the emulsion was filtered, and the solid was collected, washed with anhydrous ethanol, and filtered until the pH of the filtrate was 7. The solid after filtration was collected and placed in a vacuum oven at 100°C to dry to constant weight, and 1014.1g of coupling agent-modified lanthanum diaziridine phosphite was obtained; 100 mL of coupling agent KH560 was mixed with 1.5 L of 95% ethanol, and stirred at 50° C. for 30 min to obtain a coupling agent solution. Subsequently, 1000 g of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant was added to the coupling agent solution, and stirred at 80° C. for 6 h. After the reaction was completed, the emulsion was filtered, and the solid was collected, washed with anhydrous ethanol, and filtered until the pH of the filtrate was 7. The collected solid was placed in a vacuum oven at 100° C. and dried to constant weight to obtain 1014 g of coupling agent-modified environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant; S3, weighing 85 parts of nylon resin, 13.2 parts of coupling agent-modified diaziridinyl lanthanum hypophosphite, 1 part of coupling agent-modified environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 0.2 parts of antioxidant, and 0.3 parts of lubricant, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S4, feeding the premix obtained in step S3 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
[0044] Example 3 This embodiment provides a flame-retardant nylon composite material. Compared with Example 2, the only difference is that the flame-retardant nylon composite material includes the following components in parts by weight: 85 parts of nylon 6, 12 parts of lanthanum bis-aziridine hypophosphite, 2 parts of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0045] Example 4 This embodiment provides a flame-retardant nylon composite material. Compared with Example 2, the only difference is that the flame-retardant nylon composite material includes the following components in parts by weight: 85 parts of nylon 6, 10 parts of lanthanum bis-aziridine hypophosphite, 4 parts of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0046] Example 5 This embodiment provides a flame-retardant nylon composite material. Compared with Example 2, the only difference is that the flame-retardant nylon composite material includes the following components in parts by weight: 85 parts of nylon 6, 13 parts of lanthanum bis-aziridine hypophosphite, 1 part of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 0.5 parts of composite synergist, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0047] The composite synergist comprises 0.3 parts of polyurethane modified expanded graphite, 0.1 parts of polyethylene polyether modified carbon nanotubes and 0.1 parts of melamine polyphosphate.
[0048] The polyurethane modified expanded graphite is obtained by the following preparation method: using concentrated nitric acid to acid-treat the expanded graphite for 2 hours to increase the oxidized groups on the surface of the expanded graphite, then washing with deionized water to neutrality and drying, adding the treated expanded graphite to DMSO for ultrasonic dispersion, slowly adding the polyurethane prepolymer solution dissolved in DMSO to the dispersion of the expanded graphite, adding 0.1% of organic tin, stirring and reacting for 8 hours, after the reaction is completed, filtering out the unreacted solvent and impurities, and evaporating and drying to obtain the polyurethane modified expanded graphite.
[0049] Polyvinyl polyether modified carbon nanotubes are obtained by the following preparation method: the carbon nanotubes are acid-treated with concentrated sulfuric acid for 2 hours, then washed with deionized water until neutral and dried, the polyvinyl polyether is dissolved in acetone, the treated carbon nanotubes are added to the polyvinyl polyether solution for ultrasonic dispersion, and the reaction is continued for 8 hours. After the reaction is completed, the unreacted solvent and impurities are filtered out, and the polyvinyl polyether modified carbon nanotubes are obtained after evaporation and drying.
[0050] Example 6 This embodiment provides a flame-retardant nylon composite material. Compared with Example 5, the only difference is that the flame-retardant nylon composite material includes the following components in parts by weight: 85 parts of nylon 6, 13 parts of lanthanum bis-aziridine hypophosphite, 1 part of environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant, 3 parts of composite synergist, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0051] The composite synergist comprises 1.5 parts of polyurethane modified expanded graphite, 1 part of polyethylene polyether modified carbon nanotubes and 0.5 part of melamine polyphosphate.
[0052] Comparative Example 1 This embodiment provides a flame-retardant nylon composite material. Compared with Example 1, the only difference is that the flame-retardant nylon composite material includes the following components in parts by weight: 85 parts of nylon 6, 14 parts of diethyl aluminum hypophosphite flame retardant, 0.3 parts of lubricant A-C541A, 0.2 parts of antioxidant 1098, and 0.2 parts of coupling agent KH560.
[0053] The flame retardant nylon composite material is obtained by the following preparation method: S1. Vacuum drying the nylon resin to make its moisture content lower than 0.05%; S2. Mix 100 mL of coupling agent KH560 with 1.5 L of 95% ethanol, stir at 50 ° C for 30 min to obtain a coupling agent solution, then take 1000 g of diethyl aluminum hypophosphite flame retardant and add it to the coupling agent solution, stir at 80 ° C for 6 h, filter the emulsion after the reaction, collect the solid, wash with anhydrous ethanol, and filter until the pH of the filtrate is 7, collect the filtered solid and place it in a vacuum oven at 100 ° C to dry to constant weight, and obtain 1014 g of coupling agent-modified diethyl aluminum hypophosphite flame retardant; S3, weighing 85 parts of nylon resin, 14.2 parts of coupling agent-modified diethyl aluminum hypophosphite flame retardant, 0.2 parts of antioxidant, and 0.3 parts of lubricant, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S4, feeding the premix obtained in step S3 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
[0054] Comparative Example 2 This embodiment provides a flame retardant nylon composite material, which is different from the embodiment 1 in that: The flame retardant nylon composite material is obtained by the following preparation method: S1. Vacuum drying the nylon resin to make its moisture content lower than 0.05%; S2, weighing 85 parts of nylon resin, 14 parts of lanthanum diaziridinyl hypophosphite, 0.2 parts of coupling agent, 0.2 parts of antioxidant, and 0.3 parts of lubricant, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S3, feeding the premix obtained in step S2 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
[0055] The weight parts of the raw material components of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1.
[0056] Table 1. Raw material components of Examples 1-6 and Comparative Examples 1-2
[0057] The prepared flame retardant nylon composite materials were tested according to the test standards. The performance test results of the flame retardant nylon composite materials prepared in Examples 1-6 and Comparative Examples 1-2 are shown in Table 2.
[0058] Table 2 Performance test results of flame retardant nylon composite materials of Examples 1-6 and Comparative Examples 1-2
[0059] According to the test results, the flame retardancy of the flame retardant nylon composite materials prepared in Examples 1-6 can reach V-0 level, and the smoke density is low, the heat deformation temperature and decomposition temperature are high, reflecting excellent flame retardancy and heat resistance. In addition, the test results of various mechanical properties of the flame retardant nylon composite materials prepared in Examples 1-6 are excellent, the odor level is low, it is safer, and the application range is wider, and it can be applied to interior parts products.
[0060] By comparing Example 1 with Comparative Example 1, it can be seen that the flame retardant properties of the bis-aziridine-based lanthanum hypophosphite flame retardant selected in the present invention are far superior to the traditional diethyl aluminum hypophosphite flame retardant, have higher stability and safety performance, and have less effect on the mechanical properties of the nylon matrix, and can maintain better tensile strength and flexural strength.
[0061] By comparing Example 1 and Comparative Example 2, it can be seen that in the preparation process of the present invention, the coupling agent is first coated on the outside of the flame retardant, and then the flame retardant modified by the coupling agent is blended, so that the flame retardant can be dispersed more evenly and has better compatibility with the nylon matrix, reducing the precipitation of the flame retardant, thereby improving the mechanical properties of the composite material and enhancing the flame retardant effect of the material to a certain extent.
[0062] By comparing Example 1 with Examples 2-4, it can be seen that the compounding effect of lanthanum bis-aziridine hypophosphite and environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is better than that of a single lanthanum bis-aziridine hypophosphite flame retardant. This is because the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant can form a ceramic-like protective layer to isolate heat and combustible gases, and can also reduce the odor of the material, and absorb smoke, thereby increasing the smoke release caused by the combustion of the material. However, the addition amount of the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is not easy to be excessive, and its excessive addition will reduce the elongation at break and notched impact strength of the material, resulting in the loss of mechanical properties of the material. Therefore, it is preferred to control the mass ratio of lanthanum bis-aziridine hypophosphite and environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant to 10: (1-2).
[0063] By comparing Example 2 with Example 5-6, it can be seen that the composite synergist can cooperate with the composite flame retardant of the present invention, further optimize the flame retardant effect of the flame retardant, and promote the uniform dispersion of the flame retardant, thereby improving the mechanical properties of the material. This is because the modified expanded graphite in the composite synergist can strengthen and repair the carbon layer formed by the combustion of bis-aziridine lanthanum hypophosphite, the modified carbon nanotubes reduce heat accumulation, and the polyphosphate melamine can release phosphoric acid groups and ammonia after thermal decomposition, thereby improving the flame retardant properties of the material; at the same time, the modified expanded graphite, the modified carbon nanotubes and the polyphosphate melamine can also promote the uniform dispersion of the flame retardant in the material, avoid agglomeration, thereby further improving the mechanical properties of the material.
[0064] In summary, the present invention selects a composite flame retardant compounded with lanthanum bis-aziridine phosphite and an environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant. At high temperatures, lanthanum bis-aziridine phosphite produces a dense and stable carbonized layer, and the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant forms a protective layer similar to ceramics. The two synergistically protect the nylon material and have good flame retardant properties; and the two can maintain good structural stability and chemical stability at high temperatures, thereby ensuring the durability of the flame retardant effect and improving the safety of the material. In addition, the composite synergist of the present invention has a synergistic effect on the flame retardant, the modified expanded graphite can strengthen and repair the carbonized layer produced by combustion, the modified carbon nanotubes can reduce heat accumulation, and the polyphosphate melamine can further flame retardant. The three synergistically can also reduce the viscosity of the material, promote the uniform dispersion of the flame retardant in nylon, and improve the processing performance. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0065] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A flame retardant nylon composite material, characterized in that: The composition comprises the following components in parts by weight: Nylon resin: 75-90 parts; Flame retardant: 5-18 parts; Lubricant: 0.2-1 part; Antioxidant: 0.2-1 part; Coupling agent: 0.2-1 part; The flame retardant comprises one or a mixture of two of bis-aziridinyl lanthanum hypophosphite and an environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant.
2. The flame retardant nylon composite material according to claim 1, characterized in that: The flame retardant is a composite flame retardant prepared by mixing lanthanum bisaziridinyl hypophosphite with an environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant.
3. The flame retardant nylon composite material according to claim 2, characterized in that: The mass ratio of the bis-aziridine lanthanum hypophosphite to the environmentally friendly glassy / ceramic smokeless and halogen-free flame retardant is 10:(0.5-4).
4. The flame-retardant nylon composite material according to any one of claims 1 to 3, characterized in that: The flame retardant nylon composite material also includes 0.5 to 5 parts of a composite synergist.
5. The flame retardant nylon composite material according to claim 4, characterized in that: The composite synergist comprises one or a mixture of any of modified expanded graphite, modified carbon nanotubes and polyphosphate melamine.
6. The flame retardant nylon composite material according to claim 5, characterized in that: The modified expanded graphite includes one or a mixture of polyurethane modified expanded graphite and polytetrafluoroethylene modified expanded graphite; the modified carbon nanotube includes one or a mixture of any multiple of polyvinyl polyether modified carbon nanotube, polyvinyl alcohol modified carbon nanotube and polyamide modified carbon nanotube.
7. The flame retardant nylon composite material according to claim 1, characterized in that: The relative viscosity of the nylon resin is 2.4-3.
2.
8. The flame retardant nylon composite material according to claim 1, characterized in that: The antioxidant is selected from one of oxidant 1098, antioxidant 1010, antioxidant 168, a mixture of phenols and phosphonates, or a mixture of any multiple thereof.
9. A method for preparing a flame retardant nylon composite material, characterized in that: The following steps are involved: S1, vacuum drying the nylon resin to obtain a dried nylon resin; S2, modifying the flame retardant with a coupling agent to obtain a flame retardant modified with a coupling agent; S3, weighing the dried nylon resin, coupling agent-modified flame retardant, antioxidant, lubricant and composite synergist according to proportion, putting them into a high-speed mixer, and mixing them evenly to obtain a premix; S4, feeding the premix obtained in step S3 into a twin-screw extruder from a main feeding port, using the twin-screw extruder to extrude the composite raw material, and obtaining the flame-retardant nylon composite material after cooling and pelletizing.
10. The method for preparing a flame-retardant nylon composite material according to claim 9, characterized in that: In step S2, the process of coupling agent modification of flame retardant is as follows: dissolving the coupling agent in an ethanol solution, stirring evenly to obtain a coupling agent solution, adding the flame retardant to the coupling agent solution, stirring and reacting at 70-90° C. for a period of time, filtering the emulsion after the reaction, collecting the solid, washing with anhydrous ethanol, filtering until the pH of the filtrate is neutral, collecting the filtered solid and drying it to constant weight to obtain a coupling agent modified flame retardant.
Citation Information
Patent Citations
Rare earth metal hypophosphite and preparation method and application of rare earth metal hypophosphite
CN102838098A
Flame-retardant nylon master batch and preparation method thereof
CN113831731A
High-temperature-resistant silica gel gasket and preparation method thereof
CN118406377A
Low-corrosivity flame-retardant thermoplastic resin composition
WO2016045162A1